PENGUATAN KETERAMPILAN DASAR BERTANI MELALUI EDUKASI MENYEMAI BENIH SAWI PADA ANAK USIA 8–12 TAHUN DALAMPROGRAMPENGABDIAN MASYARAKAT KKN INTERNASIONAL DI MALAYSIA - Tedy Wijaya; Ertika Fitri Lisnanti; Titik Irawati (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The International Community Service Program (KKN Internasional) in Malaysia aims to improve basic farming skills among children aged 8 to 12 by teaching mustard seed sowing as a practical learning activity that involves direct hands-on experience. The program was implemented through interactive counseling, live demonstrations, and intensive guidance to ensure that participants fully understood the technical steps involved in seed sowing, transplanting seedlings, and plant care. The results of the program showed that rockwool media provided better plant growth compared to cotton and cocopeat, as indicated by superior plant height and leaf number at each observation stage. The children’s ability to perform the sowing process independently significantly increased, along with their interest in agricultural activities. This program also helped develop values of responsibility, independence, and environmental awareness from an early age. The outcomes indicate that simple agricultural education is highly effective as a learning medium for character building and food literacy within migrant communities. It is recommended that such activities be continuously implemented to strengthen household food security and support the development of non-formal education based on agricultural practices.